2006
DOI: 10.1111/j.1365-2958.2006.05106.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic‐diGMP signal transduction systems in Vibrio cholerae: modulation of rugosity and biofilm formation

Abstract: SummaryCyclic di-guanylic acid (c-diGMP) is a second messenger that modulates the cell surface properties of several microorganisms. Concentrations of c-diGMP in the cell are controlled by the opposing activities of diguanylate cyclases and phosphodiesterases, which are carried out by proteins harbouring GGDEF and EAL domains respectively. In this study, we report that the cellular levels of c-diGMP are higher in the Vibrio cholerae rugose variant compared with the smooth variant. Modulation of cellular c-diGM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
236
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(251 citation statements)
references
References 65 publications
12
236
0
3
Order By: Relevance
“…We typically observe the concentration of c-di-GMP in the WT strain grown in Luria-Bertani (LB) media to a density of OD 600 1.0, the optical density of the cultures examined in this study, to be 0.5-2 μM. Mutation of the master high-cell-density quorum-sensing regulator of V. cholerae, hapR, locks the cells into the low-cell-density state, increasing both cdi-GMP and biofilm formation (20,33). We have found that the concentration of c-di-GMP in a ΔhapR mutant is ∼8-10 μM.…”
Section: Discussionmentioning
confidence: 99%
“…We typically observe the concentration of c-di-GMP in the WT strain grown in Luria-Bertani (LB) media to a density of OD 600 1.0, the optical density of the cultures examined in this study, to be 0.5-2 μM. Mutation of the master high-cell-density quorum-sensing regulator of V. cholerae, hapR, locks the cells into the low-cell-density state, increasing both cdi-GMP and biofilm formation (20,33). We have found that the concentration of c-di-GMP in a ΔhapR mutant is ∼8-10 μM.…”
Section: Discussionmentioning
confidence: 99%
“…In S. typhimurium, the c-di-GMP phosphodiesterase CdgR is involved in resistance to phagocyte oxidase and in the cytotoxic effect in macrophages (48). In V. cholerae, the c-di-GMP phosphodiesterase VieA regulates expression of the cholera toxin genes ctxAB (49), whereas the CdgC protein carrying the EAL and GGDEF domains is involved in the control of extracellular protein secretion and flagellar biosynthesis (50). In Pseudomonas aeruginosa, the biofilm and cytotoxicity phenotypes are mediated by different GGDEF and EAL domain proteins involved in c-di-GMP metabolism (51).…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that the adeptness of Vibrio cells at changing back and forth from either phenotypic variant would favor the variant derivative that is more fit for survival under the prevailing environment conditions, such as those encountered in a human host or on an environmental surface. Regulation of rugosity seems to be multifactorial and highly complex (5,17,26,36,37). Although there are some similarities, great differences are observed among organisms capable of expressing rugosity (3,36,37).…”
Section: Discussionmentioning
confidence: 99%